Preserved correspondence of Eduardo Blanco-Amor to Federico García Lorca - Tinnell, Roger (Madrygal. Revista de Estudios Gallegos, 2011)
Five documents (3 letters, 2 postcards and a carte de visite sent by Eduardo Blanco-Amor to Federico García Lorca have been published only partially. Here for the first time all five documents are presented whole and with explanatory notes.